Knowledge of information commodity-based business towards income generation among bumiputera entrepreneurs / Nora’ayu Ahmad Uzir, Irni Eliana Khairuddin and Norliya Ahmad Kassim - Khairuddin, Irni Eliana; Ahmad Kassim, Norliya (Faculty of Information Management, 2013)
As the world’s economy enters the information age, there are many possibilities for establishing information and knowledge-based businesses within the global information and knowledge economy. However, Bumiputera entrepreneurs have overlooked the opportunity in offering information as a commodity for income generation. This paper provides a brief review of related literature on entrepreneurs’ knowledge on information commodity-based business that leads to income generation. A novel conceptual model is developed and proposed to evaluate the information commodity resulting to income generation. The constructs of the conceptual model are based on the three dimensions namely entrepreneur opportunity, information as commodity and income generation. Exploration and exploitation on these three dimensions would lead Bumiputera entrepreneurs toward offering information as a commodity in the information industry. By adapting this model, future study will contribute to the information commodity modelling in boosting income generation among Bumiputera entrepreneurs through offering information as a commodity in the information industry.